English for international trade :For students specialized in import and export business. - College of technologies and economics in trade.Department of English
Cung cấp kiến thức cơ bản về các kỹ năng nghe, học thuật, kiểm tra từ vựng, chú giải...trong lĩnh vực ngoại thương.